Birefringence in PM fibers using the beat-length measurement technique - Shukla P.K.; Kala P.; Choudhury P.K.; Ojha S.P.; Khastgir P. (My University, 2025)
An experimental method to determine the modal birefringence characteristics of fundamental type of elliptical core polarization maintaining fibers was described. The beat-length measurement technique was used to characterize the modal birefringence. The beat-length measurement technique can be used to observe the nature of fiber. It was concluded that the fiber used in the experiment was a high birefringent (HB) fiber.